Muramyl dipeptide-based analogs as potential anticancer compounds: Strategies to improve selectivity, biocompatibility, and efficiency - Iwicka, Eliza; Hajtuch, Justyna; Dzierzbicka, Krystyna; Inkielewicz-Stepniak, Iwona (Frontiers in Oncology, 2022)
According to the WHO, cancer is the second leading cause of death in the world. This is an important global problem and a major challenge for researchers who have been trying to find an effective anticancer therapy. A large number of newly discovered compounds do not exert selective cytotoxic activity against tumorigenic cells and have too many side effects. Therefore, research on muramyl dipeptide (MDP) analogs has attracted interest due to the urgency for finding more efficient and safe treatments for oncological patients. MDP is a ligand of the cytosolic nucleotide-binding oligomerization domain 2 receptor (NOD2). This molecule is basic structural unit that is responsible for the immune activity of peptidoglycans and exhibits many features that are important for modern medicine. NOD2 is a component of the innate immune system and represents a promising target for enhancing the innate immune response as well as the immune response against cancer cells. For this reason, MDP and its analogs have been widely used for many years not only in the treatment of immunodeficiency diseases but also as adjuvants to support improved vaccine delivery, including for cancer treatment. Unfortunately, in most cases, both the MDP molecule and its synthesized analogs prove to be too pyrogenic and cause serious side effects during their use, which consequently exclude them from direct clinical application. Therefore, intensive research is underway to find analogs of the MDP molecule that will have better biocompatibility and greater effectiveness as anticancer agents and for adjuvant therapy. In this paper, we review the MDP analogs discovered in the last 10 years that show promise for antitumor therapy. The first part of the paper compiles the achievements in the field of anticancer vaccine adjuvant research, which is followed by a description of MDP analogs that exhibit promising anticancer and antiproliferative activity and their structural changes compared to the original MDP molecule.